Exploration of Islamic Religious Learning Innovation Technology with the iLearning Approach - Haryani, Hendriyati; Astriyani, Erna; Devana, Viola Tashya (Aptisi Transactions On Technopreneurship (ATT), 2021)
The field of education has an important role for a country in producing high-quality young generations so that they can be responsible for advancing the country. This important role is in line with the function of education, which is to develop abilities and shape the character and civilization of a dignified nation in order to educate the nation's life. Seeing the importance of education for the nation's next generation, it is necessary to innovate quality learning methods from childhood education to education in lectures. In this study, it will focus on improving the quality of learning methods, especially in Islamic religious lessons with the approach ilearning -which has been intensively developed for several years. Researchers will explore learning application innovations with an assessment focus seen from the feasibility component of learning applications, with the resulting structure covering 4 factors: Parental control, contribution to development skill, efficiency and motivation. In this study, the assessment will be carried out by means of interviews in the form of a questionnaire to 100 data and the population calculation method, namely slovin, will be used in this study. The results of this study found an innovative learning application that meets the four assessment criteria. In this study, the dojo application has met 4 learning application assessment criteria by successfully occupying the first position in the four assessment categories. The assessment of parental control gets a percentage of 47%, the assessment of the role of skill development factors gets a percentage of 28%, the efficiency factor gets a percentage of 31% and the last assessment factor is the motivation factor where in the assessment of this factor the dojo application gets a percentage of 31%. Judging from this assessment, the dojo application can be stated as an application that is close to the learning application criteria in accordance with 4 (four) important factors in a learning application.